La construction du sentiment moral dans les romans contemporains pour la jeunesse Le Chagrin du roi mort et Le Combat d’hiver de Jean-Claude Mourlevat - Pergher, Alizon (Romanica Silesiana, 2021)
In the past, literature for children and adolescents reflected society’s belief that young readers were not supposed to think for themselves. Stories were vehicles to provide direct, simple moral lessons. Those moralistic books reinforced gender and good / evil tropes, leaving little room for interpretation, moral grey areas and non-traditional gender roles. In this paper, we examine two contemporary books, Le Combat d’hiver (2006) et Le Chagrin du roi mort (2009), as examples of how youth literature has evolved. In both books, readers are presented with complex characters, plots and themes that encourage personal reflection. Morals are not something to be taught but rather felt.